2017
DOI: 10.1021/acsami.7b13063
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Fabricating Dielectric–Dielectric SiC@C Core–Shell Nanowires for High-Performance Electromagnetic Wave Attenuation

Abstract: Heterostructured dielectric-dielectric nanowires of SiC core and carbon shell (SiC@C) with high-performance electromagnetic wave absorption were synthesized by combining an interfacial in situ polymer encapsulation and carbonization process. This approach overcomes the shortcomings of previous reported methods to prepare carbon shell that both carbon shell and free carbon particles are formed simultaneously. In our developed approach, the core of SiC nanowires are first positively charged. Then the negative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…[ 1–5 ] Due to its significant advantages in size control, high aspect ratio, physical and chemical properties, in recent years, it attracts wide attention in emerging applications such as optical logic gates, coherent light sources, bio‐sensors, and flexible displays. [ 6–9 ] There are many different types of micro/nanostructures existed, mainly including metallic, [ 10–12 ] semiconducting (including inorganic and organic) [ 7,13,14 ] and dielectric wires, [ 15–17 ] where organic ones have been of more and more interests, due to their different intrinsic optoelectronic characteristics. [ 18 ] For example, organic molecular materials relying on intermolecular interactions (such as π–π interaction, hydrogen bond, halogen bond, and so on) can exhibit a wide range emission from the ultraviolet to the near‐infrared.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] Due to its significant advantages in size control, high aspect ratio, physical and chemical properties, in recent years, it attracts wide attention in emerging applications such as optical logic gates, coherent light sources, bio‐sensors, and flexible displays. [ 6–9 ] There are many different types of micro/nanostructures existed, mainly including metallic, [ 10–12 ] semiconducting (including inorganic and organic) [ 7,13,14 ] and dielectric wires, [ 15–17 ] where organic ones have been of more and more interests, due to their different intrinsic optoelectronic characteristics. [ 18 ] For example, organic molecular materials relying on intermolecular interactions (such as π–π interaction, hydrogen bond, halogen bond, and so on) can exhibit a wide range emission from the ultraviolet to the near‐infrared.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced graphene oxide (RGO) exhibits an enhanced dielectric loss ability toward microwaves at elevated temperature, but is easily oxidized at atmosphere [20]. It is widely considered that silicon carbide (SiC) is a good candidate for design of MA materials with high thermostability, high strength, as well as high oxidation and corrosion resistance [37,38]. However, the application of SiC in MA area is greatly limited on account of its low electrical conductivity [39].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the efficiency of silicon carbide, many dopants especially transitional metal ions such as iron and cobalt have been used. 6,7,15,18,19 In this report, we wish to investigate and understand the effect of fluorine via in situ doping during the formation of SiC. The study of effects of fluorination has been better reported in silicon nanowires than in silicon carbide nanowires (SiCNWs).…”
Section: Introductionmentioning
confidence: 99%